2012
DOI: 10.1371/journal.pone.0037541
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Alcohol Exposure Alters Behavioral and Synaptic Plasticity of the Rodent Prefrontal Cortex

Abstract: In the present study, we used a mouse model of chronic intermittent ethanol (CIE) exposure to examine how CIE alters the plasticity of the medial prefrontal cortex (mPFC). In acute slices obtained either immediately or 1-week after the last episode of alcohol exposure, voltage-clamp recording of excitatory post-synaptic currents (EPSCs) in mPFC layer V pyramidal neurons revealed that CIE exposure resulted in an increase in the NMDA/AMPA current ratio. This increase appeared to result from a selective increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
239
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 221 publications
(265 citation statements)
references
References 62 publications
20
239
6
Order By: Relevance
“…With regard to synaptic plasticity, in the present study, CIE treatment induced a sustained increase in glutamatergic signaling following a spike-timing dependent LTP protocol that was similar to that reported for deep-layer neurons in the prelimbic sub-division of the mPFC (Kroener et al, 2012). Although the cellular mechanisms underlying these changes are not completely understood, they likely arise from a combination of changes in factors that control intrinsic excitability and excitatory synaptic signaling.…”
Section: Cie and Glutamatergic Signalingsupporting
confidence: 80%
See 4 more Smart Citations
“…With regard to synaptic plasticity, in the present study, CIE treatment induced a sustained increase in glutamatergic signaling following a spike-timing dependent LTP protocol that was similar to that reported for deep-layer neurons in the prelimbic sub-division of the mPFC (Kroener et al, 2012). Although the cellular mechanisms underlying these changes are not completely understood, they likely arise from a combination of changes in factors that control intrinsic excitability and excitatory synaptic signaling.…”
Section: Cie and Glutamatergic Signalingsupporting
confidence: 80%
“…These findings add to a growing understanding of ethanol-induced changes in glutamate receptor function and expression in the frontal cortex and confirm that such changes are both region and WD time dependent. For example, two previous studies from our group that used the same CIE protocol reported either no significant change in NMDA receptor expression in lOFC at 0 or 7 days post WD , or an increase in GluN1 and GluN2B expression in the mPFC at the 0 but not 7 day WD time point (Kroener et al, 2012). A similar increase in GluN2B expression in the mPFC was reported for CIE-exposed rats killed 3 h after the last ethanol vapor treatment (Kim et al, 2014), while no change in GluN1 or GluN2(A/B) was noted 1 week post WD (TranthamDavidson et al, 2014), despite an increase in NMDAmediated EPSCs.…”
Section: Cie and Glutamatergic Signalingmentioning
confidence: 88%
See 3 more Smart Citations